Antitumor Effects of Quercetin and Luteolin in A375 Cutaneous Melanoma Cell Line Are Mediated by Upregulation of P-ERK, c-Myc, and the Upstream GPER - Shaymaa A. Hussein; Nidaa A. Ababneh; Noor Tarawneh; Mohammad A. Ismail; Abdalla Awidi; Shtaywy Abdalla (Life)
Cutaneous melanoma (CM) is the most aggressive and fatal malignancy among other skin cancers and its incidence has risen steadily recently around the world. Hormone-related therapy, particularly estrogen (E2) has been used as a prospective strategy for CM treatment. Quercetin and luteolin are flavonoids with antitumor effects against a wide range of cancers including CM. However, the underlying mechanism of their actions through GPER in CM is not fully understood. We examined the anti-tumor effects of quercetin and luteolin on the A375 CM cell line through activation of the G-protein coupled estrogen receptor (GPER). MTT assay was performed to assess the impact of flavonoids on cell viability. Apoptosis and cell cycle were studied by flow cytometry. Cell migration was evaluated by transwell assay. GPER expression and the effect of the flavonoids on the key signaling proteins were confirmed by immunofluorescence staining and Western blot, respectively. Results showed that quercetin and luteolin inhibited proliferation and migration, induced apoptosis, and blocked the cell cycle at S and G2/M in A375 cells. Immunofluorescence and immunoblotting data demonstrated the presence of GPER in this cell line and the two flavonoids enhanced its expression except at the high concentration of 100 µM. Quercetin and luteolin enhanced P-ERK and c-Myc expression, an effect abolished by the GPER antagonist G15, confirming GPER-mediated signaling. In conclusion, quercetin and luteolin exhibited anti-tumor effects on A375 melanoma cells via GPER activation, suggesting their potential as anti-melanoma therapeutics.